2016
DOI: 10.1093/icvts/ivv379
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation as a bridge to lung transplantation: what lessons might we learn from volume and expertise?

Abstract: Lowest volume centres have lowest survival and there exists a volume threshold at which better outcomes are achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…In a United Network for Organ Sharing (UNOS) review, Hayanga and colleagues (27) showed an adjusted hazard ratio for mortality of 2.74 for patients who were bridged to lung transplantation with ECMO in a low-volume center (i.e., 1-5 transplants/year) versus a high-volume center (i.e., >15 transplants/year). This is an important consideration and suggests that transportation from a low-volume center to a higher-volume center may be wise, from both a risk and quality standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…In a United Network for Organ Sharing (UNOS) review, Hayanga and colleagues (27) showed an adjusted hazard ratio for mortality of 2.74 for patients who were bridged to lung transplantation with ECMO in a low-volume center (i.e., 1-5 transplants/year) versus a high-volume center (i.e., >15 transplants/year). This is an important consideration and suggests that transportation from a low-volume center to a higher-volume center may be wise, from both a risk and quality standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ECMO is not considered a contraindication for lung transplantation in most, but still not all, centers. Recent data demonstrate 1‐year survival rates of >70% in patients successfully bridged to lung transplant using this novel concept and are comparable to those patients without ECMO support prior to lung transplantation …”
Section: Discussionmentioning
confidence: 93%
“…As we decided to use our DCS in these clinical settings, the cannulas ( 4,7,19 Comparable to other tertiary ECMO centers that implemented the ambulatory ECMO approach in their clinical settings, we started with a single cannula strategy using the Avalon© double-lumen cannula.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Of these 26 centers, 12 performed one or less transplant using ECLS, while 14 performed >1 lung transplant using ECLS as a bridge (24). Two recent studies examining the UNOS registry showed that the overall one-year survival of patients bridged to lung transplant using ECLS in centers with greater volumes and ECLS experience were significantly higher than those with lower volumes/experience (20,24). Likewise, several single-center studies have reported oneyear survivals similar to non-ECMO bridged patients (25)(26)(27)(28)(29).…”
Section: Current Trends In Utilization and Outcomesmentioning
confidence: 99%
“…Initial studies after the inception of LAS scoring noted that one-year outcomes in patients with higher LAS (17) and patients bridged with ECMO were lower (18,19). However, more recent studies analyzing the UNOS database have showed that outcomes in ECMO patient's post-lung transplant may be similar to non-ECMO patients, especially in centers with higher transplant volumes and experience (20,21).…”
Section: Introductionmentioning
confidence: 99%